First - principles investigation of magnetism of the rare - earth hexaboride RB6 (R = La, Ce, Nd, Sm, Eu) - Chunfeng; N, Tsogbadrakh; Lihong Bao; O, Tegus; Kh, Tsookhuu (Scientific transaction of the National University of Mongolia. Physics, 2022)
Electronic and magnetic properties of the RB6 (R = La, Ce, Nd, Sm and Eu) crystals were investigated by using the first - principles method within the framework of the density functional theory. The ground state of lanthanum hexaboride (LaB6) is nonmagnetic crystal, while the others RB6 (R = Ce, Nd, Sm and Eu) are ferromagnetic crystal due to the partial occupations of electrons on 4f orbital for rare – earth atoms. We have done the prediction of lattice parameters, magnetic moments of magnetic ions and total magnetizations of the RB6 crystals. PACS numbers: 71.20.Eh, 75.50.-y